PEMAHAMAN UMAT TENTANG SAKRAMEN TOBAT DI STASI SANTO YUSUF NGREJO PAROKI ST. MARIA TAK BERNODA, KEPANJEN, MALANG - Dolorosa, Agata Graciavia; Ardijanto, Don Bosco Karnan (CREDENDUM: Jurnal Pendidikan Agama, 2019)
Although the Church suggests receiving the Sacrament of Penance at least once a year, it is not uncommon for people to reluctantly accept this sacrament due to various reasons, such as the distance from their homes to the church or living in rural areas. Based on these issues, the research question can be formulated as follows: How do the people of Stasi St. Joseph Ngrejo of St. Immaculata Mary Parish Kepanjen Malang understand the Sacrament of Penance? This study aims to gain a deeper understanding of the parishioners' knowledge of the sacrament. The study uses a qualitative approach, with interviews as the data collection method. Ten respondents, selected through purposive sampling, were active church members who did not hold any official positions, but were stewards or activists of the church. The research was conducted at the Stasi St. Joseph Ngrejo of St. Immaculata Mary Parish Kepanjen Malang. The findings indicate that most of the people already have an understanding of the Sacrament of Penance, which is also known by another name.